2014
DOI: 10.1007/s12350-013-9787-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of left ventricular mechanical dyssynchrony by phase analysis in patients with non-ischemic cardiomyopathy with ejection fraction 35-50% and QRS < 150 ms

Abstract: In patients with NICM, EF 35-50%, and QRS < 150 ms, increased LVMD on peak stress SPECT was an independent predictor of all-cause mortality. The utility and applicability of such findings in clinical practice need further evaluation in larger and prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…11 The initial application of the technique was in identifying the optimal patients with cardiomyopathy who would derive most benefit from cardiac resynchronization therapy. 12 Since then, the technique proved not only to be a valuable tool in detecting mechanical dyssynchrony, but also providing prognostic information and risk stratifying patients with various co-morbidities (ischemic, 13 non-ischemic cardiomyopathy, 14 implantable defibrillators, 15 end-stage renal disease 16,17 ). More recently, the technique has been used to detect ischemiainduced myocardial dyssynchrony and multi-vessel CAD by comparing stress and rest indices [18][19][20] ( Table 1).…”
Section: See Related Article Pp 1048-1056mentioning
confidence: 99%
“…11 The initial application of the technique was in identifying the optimal patients with cardiomyopathy who would derive most benefit from cardiac resynchronization therapy. 12 Since then, the technique proved not only to be a valuable tool in detecting mechanical dyssynchrony, but also providing prognostic information and risk stratifying patients with various co-morbidities (ischemic, 13 non-ischemic cardiomyopathy, 14 implantable defibrillators, 15 end-stage renal disease 16,17 ). More recently, the technique has been used to detect ischemiainduced myocardial dyssynchrony and multi-vessel CAD by comparing stress and rest indices [18][19][20] ( Table 1).…”
Section: See Related Article Pp 1048-1056mentioning
confidence: 99%
“…It was shown to predict ICD shock, 14 and all-cause mortality. 15,16 In addition, it was tested and validated with PET imaging. 17 However, phase analysis faced several challenges…”
mentioning
confidence: 99%
“…It was shown to predict ICD shock, 14 and all-cause mortality. 15,16 In addition, it was tested and validated with PET imaging. 17 However, phase analysis faced several challenges including; (1) different vendors have different software and values without any way to standardize; (2) limited temporal resolution despite complex mathematical way to bypass it; (3) noise and artifact from areas with significantly reduced perfusion due to scar; (4) SPECT myocardial perfusion imaging is not performed routinely prior to CRT unlike echocardiography; and (5) limited data post-CRT placement as it requires repeat testing and tracer injection.…”
mentioning
confidence: 99%
“…8 It was found that PSD and PBW were associated with a significantly higher incidence of MACE (P \ 0.001) and proved to a strong predictor of MACE independent of other known predictors such as perfusion defects or decreased leftventricular ejection fraction (LVEF). Goldberg et al 9 enrolled 324 consecutive patients with non-ischemic cardiomyopathy (NICM), LVEF 35%-50%, and QRS \ 150 ms and found that the patients who died had a trend toward a higher mean PSD (P = 0.1) and PBW (P = 0.08). After adjusting for age, hypertension, diabetes, aspirin, beta-blockers, diuretics, QRS, and LVEF, PSD and PBW were independent predictors of all-cause mortality and added incremental prognostic value (P = 0.025 for PSD).…”
mentioning
confidence: 99%